Peptides-Coated Oncolytic Vaccines for Cancer Personalized Medicine - Feola, Sara; Russo, Salvatore; Martins, Beatriz; Lopes, Alessandra; Vandermeulen, Gaëlle; Fluhler, Vinciane; De Giorgi, Camilla; Fusciello, Manlio; Pesonen, Sari; Ylösmäki, Erkko; Antignani, Gabriella; Chiaro, Jacopo; et al. (Frontiers in Immunology, 2022)
Oncolytic Viruses (OVs) work through two main mechanisms of action: the direct lysis of the virus-infected cancer cells and the release of tumor antigens as a result of the viral burst. In this scenario, the OVs act as in situ cancer vaccines, since the immunogenicity of the virus is combined with tumor antigens, that direct the specificity of the anti-tumor adaptive immune response. However, this mechanism in some cases fails eliciting a strong specific T cell response. One way to overcome this problem and enhance the priming efficiency is the production of genetically modified oncolytic viruses encoding one or more tumor antigens. To avoid the long and expensive process related to the engineering of the OVs, we have developed an approach based on coating OVs with tumor antigens. In this work, we have compared oncolytic viruses encoding tumor antigens and oncolytic adenovirus decorated with tumor antigen (PeptiCRAd); we have evaluated their immunogenicity and their prophylactic and therapeutic efficacy. We have first tested the oncolytic vaccines by exploiting the OVA model, moving then to TRP2, a more clinically relevant tumor antigen. Finally, both approaches have been investigated in tumor neo-antigens settings. Our data show that both genetically modified oncolytic adenovirus and PeptiCRAd elicited a comparable and strong T cells-specific anti-tumor responses. In vitro cross-representation experiments showed that PeptiCRAd elicited a faster presentation of antigens compared to a genetic vaccine. In vivo analysis showed a comparable immunogenicity and tumor control with OVA model, with a more clinically relevant model such as TRP2 we observed a better tumor control of PeptiCRAd compared with genetic vaccine, probably as result of better priming of T cells. With a neo-antigen model, we observed a comparable tumor control in the treated tumor but a better tumor control in the untreated tumors, probably once again reflecting a better timing of T cell priming. We concluded that there is not a significant immunological difference between a genetic vaccine and our PeptiCRAd; however, PeptiCRAd retains the advantage of the cost, the time to produce and the adaptability of the system, crucial features for the development of personalized cancer vaccines.